2018
DOI: 10.37358/rc.18.10.6637
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Biochemical and Clinical Characteristics of Resistant Hypertension

Abstract: The objectives of the present study were to evaluate the prevalence of resistant hypertension (RH) in primary care setting and to analyse its biochemical and clinical characteristics. After 3 months of treatment and evaluation, 721 (14.01%) of 5,146 patients with hypertension did not reach target office blood pressure of [ 140/90 mmHg. After exclusion of �white-coat effect� with ambulatory blood pressure, of secondary and pseudo- resistant hypertension, prevalence of RH was 6.74%. Lifestyle factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In a cross-sectional survey conducted in a primary care population, the prevalence of CKD in patients with hypertension was 21%, the most frequent stage being stage 3 CKD [14]. As noticed in our study, the presence of CKD was associated with old age, female gender, high values of systolic BP and diabetes mellitus [15][16][17]. In the SEPHAR II Survey (2012) regarding the evaluation of hypertension in Romania, microalbuminura was present in 7.1%, macroproteinuria in 1.4%, mild renal impairment with eGFR 90-60 mL/min/m 2 in 41% and moderate severe renal impairment with eGFR <60 mL/min/1.73m 2 in 5.6%.…”
Section: Resultssupporting
confidence: 78%
“…In a cross-sectional survey conducted in a primary care population, the prevalence of CKD in patients with hypertension was 21%, the most frequent stage being stage 3 CKD [14]. As noticed in our study, the presence of CKD was associated with old age, female gender, high values of systolic BP and diabetes mellitus [15][16][17]. In the SEPHAR II Survey (2012) regarding the evaluation of hypertension in Romania, microalbuminura was present in 7.1%, macroproteinuria in 1.4%, mild renal impairment with eGFR 90-60 mL/min/m 2 in 41% and moderate severe renal impairment with eGFR <60 mL/min/1.73m 2 in 5.6%.…”
Section: Resultssupporting
confidence: 78%
“…Analysis of the circadian pattern in hypertension with CKD, compared to hypertension without CKD, indicated the prevalence of an unfavourable non-dipping pattern in 66.9%. Studies have demonstrated that the inadequate BP control in these patients is https://doi.org/10.37358/RC.20.7.8260 associated with a greater incidence of target organ damage and of cardiovascular diseases [12][13][14]. Similar data concerning the circadian pattern were found by Gorostidi et al on the database of the Spanish Hypertension ABPM Registry [2,14].…”
Section: Resultsmentioning
confidence: 53%